Pathophysiological aspects of Aspergillus colonization in disease. (15th September 2018) - Gago, Sara; Denning, David W; Bowyer, Paul
Abstract: Aspergillus colonization of the lower respiratory airways is common in normal people, and of little clinical significance. However, in some patients, colonization is associated with severe disease including poorly controlled asthma, allergic bronchopulmonary aspergillosis (ABPA) with sputum plugs, worse lung function in chronic obstructive pulmonary aspergillosis (COPD), invasive aspergillosis, and active infection in patients with chronic pulmonary aspergillosis (CPA). Therefore, understanding the pathophysiological mechanisms of fungal colonization in disease is essential to develop strategies to avert or minimise disease. Aspergillus cell components promoting fungal adherence to the host surface, extracellular matrix, or basal lamina are indispensable for pathogen persistence. However, our understanding of individual differences in clearance of A. fumigatus from the lung in susceptible patients is close to zero.